Sistem Pengelolaan Dana Berkelanjutan Berbasis Kemandirian Ekonomi di Pesantren An Nahdliyin Lerang - Sapriadi, Nia Rahmadani; Majid, Jamaluddin; Shadriyah, Shadriyah (Islamic Banking and Finance, 2024)
This study aims to analyze the fund management system based on economic independence at Pesantren An Nahdliyin Lerang, South Sulawesi, as well as its challenges and impacts on operational sustainability and the empowerment of students (santri). The approach used is qualitative-descriptive, with data collected through in-depth interviews and direct observations of fund management practices. The results of the study indicate that the pesantren has successfully implemented three main principles: economic independence, student empowerment, and profit distribution based on welfare. Economic independence is achieved through the development of agribusiness and other productive ventures, which reduce reliance on external donations. Student empowerment is evident in their direct involvement in economic activities, equipping them with practical skills. Profit distribution based on welfare ensures that the proceeds from economic activities are used for operational needs and improving educational facilities. This study concludes that the fund management system based on economic independence at Pesantren An Nahdliyin Lerang not only supports operational sustainability but also contributes to the empowerment of the surrounding community.